Hydronephrosis – a case report in a 88-year-old man - Wróbel, Grzegorz (Journal of Education, Health and Sport, 2017)
Hydronephrosis is a condition where urine overfills, or backs up, into the kidney, which causes the kidney to stretch (dilate), much like a balloon when it is filled with water. Hydronephrosis can be congenital or acquired (functional or anatomical). The aim of the study is to investigate the case of left kidney taken from human corpses (82-year-old man) with morphological changes corresponding to hydronephrosis. In the anatomical aspect, the hydrogel formation process is as follows: above the obstruction in the ureters (e.g. stone or a tumour) the urinary tracts expand. Followed by impaired blood supply, kidney parenchyma disappears and kidneys transform themselves in a bag filled with urine. Causes are numerous. Various congenital deformities of the ureter may sooner or later produce back pressure. Kidney stones are a common cause. In older men, the continued growth of the prostate gland leads commonly to restricted urine flow out of the bladder. Prostate cancer, and cancer anywhere else along the urine pathways, can obstruct flow.